2021
DOI: 10.1108/ijicc-12-2020-0212
|View full text |Cite
|
Sign up to set email alerts
|

Multi-objective vendor managed inventory system with interval type-2 fuzzy demand and order quantities

Abstract: PurposeThe proposed IT2FMOVMI model intends to concurrently minimize total cost and warehouse space for the single vendor-retailer, multi-item and a consolidated vendor store. Regarding demand and order quantities with the deterministic and type-1 fuzzy numbers, we have also formulated the classic/crisp MOVMI model and type-1 fuzzy MOVMI (T1FMOVMI) model. The suggested solution technique can solve both crisp MOVMI and T1FMOVMI problems. By finding the optimal ordered quantities and backorder levels, the Pareto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…A robust single fuzzifier IT2 fuzzy C-means clustering method to adopt the interval-valued numbers for the application of land cover segmentation was presented by Wu and Gao [27]. Ashraf and shahid [28] established the multiobjective vender managed model with IT2FNs for demand and order quantity. Javanmard et al [29] demonstrated a fuzzy solution to a linear programming problem where all coefficients are understood by IT2 FNs.…”
Section: A Interval Type-2 Fuzzy Set and Applicationsmentioning
confidence: 99%
“…A robust single fuzzifier IT2 fuzzy C-means clustering method to adopt the interval-valued numbers for the application of land cover segmentation was presented by Wu and Gao [27]. Ashraf and shahid [28] established the multiobjective vender managed model with IT2FNs for demand and order quantity. Javanmard et al [29] demonstrated a fuzzy solution to a linear programming problem where all coefficients are understood by IT2 FNs.…”
Section: A Interval Type-2 Fuzzy Set and Applicationsmentioning
confidence: 99%
“…They used Imperialist Competitive Algorithm (ICA) to solve the model. Ashraf and Shahid (2021) suggested a multiobjective VMI system with interval type-2 fuzzy demand and order quantities. They applied NSGA-II with EKM (Enhanced Karnink-Mendel) algorithm.…”
Section: Application Of Vmi In Scmentioning
confidence: 99%
“…By restricting the number of features considered at each split, the base estimators are forced to make more independent decisions, which can lead to a more robust The BBC combines the advantages of bagging and sampling techniques to address the issue of imbalanced datasets [20]. Several researchers in recent times and the past have recommended fuzzy logic (e.g., [11], [20], [21], [22], [23], [24], [25]). The objective is to add human-centric design along with advanced machine-learning algorithms.…”
Section: Modeling and Evaluationmentioning
confidence: 99%